Otras historias de procesalistas y del proceso - CACHÓN CADENAS, MANUEL-JESÚS (Historia del Derecho, 2022)
This work is a complement and continuation of the book by the same author Historias de procesalistas, universidades y una guerra civil (1900-1950) (Universidad Carlos III de Madrid/ed. Dykinson, Madrid, 2012), and includes various works written in recent years and referring to proceduralists of the more or less recent past. For these purposes, the concept of proceduralist is understood in a broad sense, which includes not only jurists who were professionally dedicated to this subject, but also other jurists who, repeatedly or occasionally, published studies of procedural content. In some of these works, an attempt has been made to reconstruct the life, academic and scientific trajectory of a proceduralist. Other writings deal with specific facts concerning the life of a particular proceduralist which have had a special impact on the history of Procedural Law. There are also several studies which, without referring to a specific proceduralist, analyse different procedural issues which concerned our ancestors, contributed to shaping the current procedural system and can help to understand it. The main objective of the compilation is to facilitate the search for the compiled works for those readers who may be interested in the issues dealt with in the corresponding writings. In the edition note at the back of the book, the publications in which the studies compiled in this work were published are indicated, but the version in which they were published is maintained in full. The compiled works follow the chronological order of the events studied in each of them.